Composição química, toxicidade e atividade biológica de Vatairea macrocarpa (Benth.) Ducke (Leguminosae) - Valadares, Sammya Nayara Silva (2017)
The species Vatairea macrocarpa (Benth.) Ducke is typical of Brazil, popularly known as maleiteira, angelim-do-cerrado and bitter, and is popularly used to treat various pathologies. The present study had as objective to evaluate the chemical chemistry, a toxicity and biological potential of extracts of leaves and stem of V. macrocarpa. The extracts were obtained by maceration in methanol.The chemical composition was analyzed by Thin Layer Chromatography (TLC). Phenoliccompounds, flavonoid and antioxidant activity tests were performed using the diphenylpicrilhydrazyl radical sequestration method (DPPH) and the β-carotene / linoleic acid co-oxidation method. The acute toxicity test and the motor coordination evaluation were performed by the rota-rod test, as well as the tests for the evaluation of the anti-inflammatory activity (carrageenan-induced paw edema) and analgesic (acetic acid, formalin and hot plate). In the extracts the presence of flavonoids, steroids, terpenes, coumarins, saponins and absence of alkaloids were identified. The content of phenolic compounds and flavonoids were determined and both extracts presented antioxidant activity in both methods. No toxic signs were observed for both extracts at the fixed dose of 300 mg / kg or changes in the motor coordination of the animals at the doses tested. Both the stem and the leaves showed antinociceptive and anti-inflammatory activity in the tests performed. In view of the promising results presented by this species it is necessary to continue the studies with the same in order to isolate and identify substances and elucidate their mechanisms of action regarding the anti-inflammatory and analgesic activities.